FEATURES OF TREATMENT TACTICS FOR PATIENTS WITH «HIGH RISK» ACUTE OBSTRUCTIVE CHOLECYSTITIS - D.A. ABDULLOZODA; L.A. GULOMOV; A.M. SAFARZODA (Avicenna Tajik State Medical University, 2020)
Objective: To improve the results of surgical treatment of patients with high operational and anesthetic risk, the suffering of acute obstructive cholecystitis (AOC), by improving two-stage tactics. Methods: From 2015 to 2019, 158 patients with AOC who had several concomitant diseases or a long period of the main pathology before hospitalization were subjected to surgical treatment. The age of patients ranged from 50 to 90 years. Patients were divided into 2 groups: the first group (control) - 74 (46.8%) patients who underwent decompression of the biliary system through cholecystostomy for 3 to 10 days; the second group (main) - 84 (53,2%) patients who, in addition to the above manipulations, underwent intracystic laser therapy through cholecystostomy. Results: All patients with AOC who had a high operational and anesthetic risk were subjected to a two-stage surgical tactic, which consisted of cholecystic decompression (first stage) followed by cholecystectomy (second stage). Group I patients received the generally accepted two-stage tactics followed by traditional cholecystectomy. Patients of group II at the second stage underwent laparoscopic cholecystectomy. Intraoperative complications in patients of group I: bleeding - 2.63%, iatrogenic damage to the common bile duct - 0.1%. In the postoperative period, seroma observed in 14.3% of cases, postoperative wound infiltrate in 11.9%, suppuration in 9.52%, peritonitis in 1.76% (required re-operation). The lethality in this group was 4.05% (3 cases). No intraoperative complications have been reported to the main group. In the postoperative period, seroma occurred in 5.2% of cases, infiltrate in 2.63%, and postoperative wound suppuration in 2.63%. The mortality in this group was observed in one case (1.19%). Conclusion: The use of laser therapy through cholecystostomy during bile duct decompression helps reduce the incidence of intra- and postoperative complications, improves the results of surgical treatment and the quality of life of patients.